Prediction for lateral deformation capacity of corroded reinforced concrete columns. (18th October 2018) - Cheng, Hu; Li, Hong‐Nan; Wang, Dong‐Sheng
Summary: The deformation capacities of columns, which are the main lateral force‐resisting elements of reinforced concrete (RC) structures, have been the subject of great interest with the development of performance/displacement‐based seismic design. However, deterioration due to chloride‐induced corrosion causes a significant reduction in the seismic performance of RC columns. Although numerous investigations have focused on the deformation capacity of columns with corroded rebars and various strengthening measures have been proposed, little attention was paid to evaluating the contribution of each deformation component to the tip displacement under corrosion (i.e., bending, shear, and longitudinal bar slip at the column footing), which plays an important role in investigating and explaining the failure mechanisms of columns. This paper presents a computational prediction model to estimate the deformation capacity of RC columns with corroded rebars, and the contributions of bending and bar slip at the column footing are mainly considered in this model due to the negligible contribution of the shear deformation component for columns subjected to flexural failure mode. The calculation results obtained by the prediction model are compared with the quasistatic test results of both noncorroded and corroded RC columns. It turns out that the prediction model simulates the deformation capacity of RC columns with corroded rebars reasonably well considering its simplicity and computational efficiency, and it can be used for time‐variant capacity estimates for the lifetime seismic design and fragility assessment of RC columns exposed to corrosion.